2011
DOI: 10.1091/mbc.e10-06-0487
|View full text |Cite
|
Sign up to set email alerts
|

The Zds proteins control entry into mitosis and target protein phosphatase 2A to the Cdc25 phosphatase

Abstract: Protein phosphatase 2A (PP2A) is a key regulator of mitosis, but the roles that it plays are poorly understood. New evidence in budding yeast shows that the Zds proteins form a tight stoichiometric complex with PP2A and target its activity to the Cdc25 phosphatase, which is a key regulator of entry into mitosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 83 publications
(141 reference statements)
3
67
0
Order By: Relevance
“…The proteins Zds1 and Zds2, which associate with and regulate PP2A Cdc55 (Yasutis et al 2010;Wicky et al 2011) help tip the kinase-phosphatase balance in favor of Cdk1 (Queralt and Uhlmann 2008b). They probably accomplish this by binding and retaining PP2A Cdc55 in the cytoplasm, thereby lowering its nuclear concentration (Rossio and Yoshida 2011), but the precise mechanism remains unclear.…”
Section: Fear Pathwaymentioning
confidence: 99%
“…The proteins Zds1 and Zds2, which associate with and regulate PP2A Cdc55 (Yasutis et al 2010;Wicky et al 2011) help tip the kinase-phosphatase balance in favor of Cdk1 (Queralt and Uhlmann 2008b). They probably accomplish this by binding and retaining PP2A Cdc55 in the cytoplasm, thereby lowering its nuclear concentration (Rossio and Yoshida 2011), but the precise mechanism remains unclear.…”
Section: Fear Pathwaymentioning
confidence: 99%
“…108,109 Suppression of this phenotype by loss of Swe1p suggested that the Zds proteins regulate the Swe1pdependent G 2 /M checkpoint. 111 In deciphering the mechanism of this regulation, Yasutis et al, 101 relying on a genetic approach that focused on Zds2p, and Wicky et al, 104 relying on a more biochemical approach that focused on Zds1p, identified Cdc55p, a regulatory subunit of PP2A, as a Zds-interacting protein. 101,104 These data are consistent with high-throughput studies (see refs.…”
Section: G 2 /M Checkpoint In S Pombe and Vertebratesmentioning
confidence: 99%
“…110) that showed protein-protein interactions between the Zds proteins and Cdc55p as well as with reports of co-immunopurification of Cdc55p and Zds1p. 104,112 Two observations position PP2A Cdc55p downstream of the Zds proteins in the G 2 /M checkpoint: (1) accelerated entry into mitosis upon Zds1p or Zds2p overexpression is Cdc55p-dependent, and (2) deletion of CDC55 suppresses the G 2 arrest phenotype (long buds) of zds1Δ zds2Δ cells. 101 These observations indicate that the Zds proteins inhibit Cdc55p at G 2 /M, allowing the transition into mitosis.…”
Section: G 2 /M Checkpoint In S Pombe and Vertebratesmentioning
confidence: 99%
“…4 Among them, the regulatory B subunit is largely responsible for the subcellular localization and substrate specificity of PP2A. 4 In budding yeast, cells lacking Cdc55 (a regulatory B subunit) exhibit multiple cell cycle defects, including mitotic entry, [5][6][7][8][9][10] spindle assembly checkpoint (SAC), 5,[11][12][13] and precocious mitotic exit. 12,[14][15][16][17][18] We have proposed previously that PP2A-Cdc55 activity is largely controlled by its subcellular distribution.…”
Section: Introductionmentioning
confidence: 99%